Percutaneous Intervention or Bypass Graft for Left Main Coronary Artery Disease? A Systematic Review and Meta-Analysis - Waqas Ullah; Yasar Sattar; Irfan Ullah; Ammu Susheela; Maryam Mukhtar; M. Chadi Alraies; Mamas A. Mamas; David L. Fischman (Journal of Interventional Cardiology)
Background. The safety and efficacy of percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG) for stable left main coronary artery disease (LMCAD) remains controversial. Methods. Digital databases were searched to compare the major adverse cardiovascular and cerebrovascular events (MACCE) and its components. A random effect model was used to compute an unadjusted odds ratio (OR). Results. A total of 43 studies (37 observational and 6 RCTs) consisting of 29,187 patients (PCI 13,709 and CABG 15,478) were identified. The 30-day rate of MACCE (OR, 0.56; 95% CI, 0.42–0.76; p = 0.0002) and all-cause mortality (OR, 0.52; 95% CI, 0.30–0.91; p = 0.02) was significantly lower in the PCI group. There was no significant difference in the rate of myocardial infarction (MI) (p = 0.17) and revascularization (p = 0.12). At 5 years, CABG was favored due to a significantly lower rate of MACCE (OR, 1.67; 95% CI, 1.18–2.36; p = <0.04), MI (OR, 1.67; 95% CI, 1.35–2.06; p = <0.00001), and revascularization (OR, 2.80; 95% CI, 2.18–3.60; p = <0.00001), respectively. PCI was associated with a lower overall rate of a stroke, while the risk of all-cause mortality was not significantly different between the two groups at 1- (p = 0.75), 5- (p = 0.72), and 10-years (p = 0.20). The Kaplan–Meier curve reconstruction revealed substantial variations over time; the 5-year incidence of MACCE was 38% with CABG, significantly lower than 45% with PCI (p = <0.00001). Conclusion. PCI might offer early safety advantages, while CABG provides greater durability in terms of lower long-term risk of ischemic events. There appears to be an equivalent risk for all-cause mortality.